Effect of natural polyphenols in Chinese herbal medicine on obesity and diabetes: Interactions among gut microbiota, metabolism, and immunity - Chen, Keyu; Gao, Zezheng; Ding, Qiyou; Tang, Cheng; Zhang, Haiyu; Zhai, Tiangang; Xie, Weinan; Jin, Zishan; Zhao, Linhua; Liu, Wenke (Frontiers in Nutrition, 2022)
With global prevalence, metabolic diseases, represented by obesity and type 2 diabetes mellitus (T2DM), have a huge burden on human health and medical expenses. It is estimated that obese population has doubled in recent 40 years, and population with diabetes will increase 1.5 times in next 25 years, which has inspired the pursuit of economical and effective prevention and treatment methods. Natural polyphenols are emerging as a class of natural bioactive compounds with potential beneficial effects on the alleviation of obesity and T2DM. In this review, we investigated the network interaction mechanism of “gut microbial disturbance, metabolic disorder, and immune imbalance” in both obesity and T2DM and systemically summarized their multiple targets in the treatment of obesity and T2DM, including enrichment of the beneficial gut microbiota (genera Bifidobacterium, Akkermansia, and Lactobacillus) and upregulation of the levels of gut microbiota-derived metabolites [short-chain fatty acids (SCFAs)] and bile acids (BAs). Moreover, we explored their effect on host glucolipid metabolism, the AMPK pathway, and immune modulation via the inhibition of pro-inflammatory immune cells (M1-like Mϕs, Th1, and Th17 cells); proliferation, recruitment, differentiation, and function; and related cytokines (TNF-α, IL-1β, IL-6, IL-17, and MCP-1). We hope to provide evidence to promote the clinical application of natural polyphenols in the management of obesity and T2DM.